2020
DOI: 10.1007/s10637-020-00939-w
|View full text |Cite
|
Sign up to set email alerts
|

Phase I study of DFP-11207, a novel oral fluoropyrimidine with reasonable AUC and low Cmax and improved tolerability, in patients with solid tumors

Abstract: Summary 5-fluorouracil (5-FU) and 5-FU derivatives, such as capecitabine, UFT, and S-1, are the mainstay of chemotherapy treatment for gastrointestinal cancers, and other solid tumors. Compared with other cytotoxic chemotherapies, these drugs generally have a favorable safety profile, but hematologic and gastrointestinal toxicities remain common. DFP-11207 is a novel oral cytotoxic agent that combines a 5-FU pro-drug with a reversible DPD inhibitor and a potent inhibitor of OPRT, resulting in enhanced pharmaco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 36 publications
(43 reference statements)
0
5
0
Order By: Relevance
“…The inhibitory activity of DFP-11207 toward DPD and orotate phosphoribosyl transferase (OPRT) was comparable to that of CDHP and CTA alone. The pharmacokinetic study suggested that DFP-11207 resulted in lower C max and AUC values but longer T max and T 1/2 values of 5-FU, respectively, than S-1, which suggested that DFP-11207 is superior to avoid the 5-FU-induced severe hematological toxicity including neutropenia, in particular, thrombocytopenia, on top of the protection of 5-FU-induced GI toxicities. , …”
Section: Strategies To Counter Dpd-mediated Resistance To 5-fumentioning
confidence: 99%
See 1 more Smart Citation
“…The inhibitory activity of DFP-11207 toward DPD and orotate phosphoribosyl transferase (OPRT) was comparable to that of CDHP and CTA alone. The pharmacokinetic study suggested that DFP-11207 resulted in lower C max and AUC values but longer T max and T 1/2 values of 5-FU, respectively, than S-1, which suggested that DFP-11207 is superior to avoid the 5-FU-induced severe hematological toxicity including neutropenia, in particular, thrombocytopenia, on top of the protection of 5-FU-induced GI toxicities. , …”
Section: Strategies To Counter Dpd-mediated Resistance To 5-fumentioning
confidence: 99%
“…The pharmacokinetic study suggested that DFP-11207 resulted in lower C max and AUC values but longer T max and T 1/2 values of 5-FU, respectively, than S-1, which suggested that DFP-11207 is superior to avoid the 5-FU-induced severe hematological toxicity including neutropenia, in particular, thrombocytopenia, on top of the protection of 5-FU-induced GI toxicities. 26,27 DPD Downregulators. Because sphingosine-1-phosphate receptor 2 (S1PR2) is closely associated with the expression of DPD in various cancer cells, inhibiting it may downregulate the DPD levels and finally reverse the 5-FU resistance.…”
Section: In Cancermentioning
confidence: 99%
“…The DPD inhibitors had combined with orally bioavailable fluorinated pyrimidine such as capecitabine or tegafur to verify the similar effect to continuous intra-venous infusion of 5-FU and did not prove molecules advantageous to continuous intra-venous infusion ( Kobayakawa and Kojima, 2011 ; Aguado et al, 2014 ). Furthermore, more oral fluoropyrimidine such as S1 (tegafur/gimeracil/oteracil) are in progress phase I clinical trials for tumors, including EC ( Ajani et al, 2020 ; Hosoda et al, 2020 ). However, up to date, the 5-FU is still the widest used fluorinated pyrimidine for cancer treatment.…”
Section: Resistance In Fluorinated Pyrimidinesmentioning
confidence: 99%
“…An in vitro study using colon adenocarcinoma cells showed that a lethal dose 50% of continuous infusion of 5-FU was approximately 100 times lower than that administered in a pulsatile manner ( 12 ). In addition, it was reported that a continuous infusion of FU demonstrated higher therapeutic efficacy and minimal side effects compared with the bolus injection ( 13 , 14 ).…”
Section: Introductionmentioning
confidence: 99%